Using Visual Basic for applications - Webb, Jeff, 1961- (Que Corp., 1994)
In this book you will learn how to record and modify macros, as well as create sophisticated Windows applications using core engines of Microsoft's most powerful programs. Expert advice shows you how to get the most from extensions that Microsoft provides, as well as how to integrate the best features of Excel 5 into your own applications.